Magnetic properties of the magnetoelectric Al2-xFexO3 (x=0.8, 0.9 and 1) - Pissas, M.; Stamopoulos, D.; Sanakis, Y; Simopoulos, A. (JOURNAL OF PHYSICS-CONDENSED MATTER, 2008)
By using x-ray diffraction, magnetization and Mossbauer spectroscopy techniques we have studied the magnetoelectric Al2-xFexO3 (x = 0.8, 0.9 and 1.0) compound. Ac-susceptibility and magnetization measurements revealed magnetic transitions at T-N = 180, 210 and 260 K for x = 0.8, 0.9 and 1.0 respectively, that can be attributed to the Neel temperatures of ferrimagnetic to paramagnetic phase transition for all samples. Mossbauer spectra for the three samples were recorded between 4.2 and 295 K. Above the Neel temperature the paramagnetic spectra can be analyzed by three quadrupole doublets associated with the octahedral Fe1, Fe2 and Fe4 sites. The values of the hyperfine parameters show that iron ions are in the high spin Fe3+ state. The spectrum area of the doublet with larger quadrupole splitting increases with x, and in combination with x-ray diffraction results it can be attributed to the iron which occupies the Fe4 site. Below T-N(x) the Mossbauer spectra are magnetically split and at T = 4.2 K consist of six broad lines, indicating either a hyperfine magnetic field distribution (P(H-hyp)) or that the three octahedral sites give three unresolved sextets. The most probable value of H-hyp (the maximum value of P(H-hyp)) follows a power law indicative of a second order transition, in agreement with ac-susceptibility and magnetization measurements. The width of P(H-hyp) increases drastically toward low hyperfine magnetic fields as temperature increases. In addition, an appreciable percentage of the iron nuclei sense a hyperfine field with values in the interval [0, H-max]. This behavior can be explained by assuming that several magnetic sites with different superexchange parameters exist.